Pengembangan Multimedia Pembelajaran Interaktif Berbantuan Software Lectora Inspire pada Sub Elemen Keamanan Pangan Bagi Siswa SMK Kuliner Fase E (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Learning media is one of the most important things in the learning process, so innovation is needed so that the media can overcome problems that exist in schools. This study focuses on the development of interactive learning multimedia assisted by lectora inspire on the sub-element of food safety for students of SMK Kuliner Phase E. The purpose of this study was to determine the feasibility of interactive learning multimedia assisted by lectora inspire software based on media expert tests, material expert tests and student responses. This research method uses R&D with the ADDIE development model, the process used through four stages, namely analysis, design, development and implementation. The data collection instruments used are material expert validation sheets, media expert validation sheets, and student response questionnaires. The data analysis technique used is quantitative descriptive analysis using a Likert scale. The results of this study show the percentage of material expert eligibility of 92%, media expert validation of 90% and student responses of 83% with very feasible criteria. Thus, interactive learning multimedia assisted by lectora inspire on the sub-element of food safety for students of SMK Kuliner Phase E that has been developed is feasible for use in learning